Maternal supportive and interfering control as predictors of adaptive and social development in children with and without developmental delays. (19th July 2013) - Green, S.; Caplan, B.; Baker, B.
Abstract Background Parents of children with developmental delays (DD) have been found to use more controlling behaviour with their children than parents of children with typical development (TD). While controlling behaviour is related to poorer developmental outcomes in TD children, there is little research on how it predicts outcomes in DD children. Furthermore, existing research tends to use inconsistent or non‐specific definitions of controlling behaviour, often combining parent control which follows the child's goal (e.g. supportive direction) and that which interferes with the child's goal (e.g. interference). Methods Participants were 200 mother–child dyads observed at child age 3, with follow‐up assessments of adaptive behaviour and social skills administered at child ages 5 and 6, respectively. We coded the frequency of both types of controlling behaviour based on mothers' interactions with their children with TD (n = 113) or DD (n = 87) at age 3. Results Mothers in the DD group used more interfering but not more supportive directive acts compared to mothers in the TD group. Adaptive behaviour was assessed at child age 5 and social skills were assessed at age 6. Higher frequency of supportive directive acts predicted better adaptive functioning for the TD group and better social skills for the DD group. Higher frequency of interfering acts predicted lower adaptive and social skills for children with DD but not with TD. Conclusions Results are discussed in terms of the differential developmental needs of children with and without DD as well as implications for early intervention.